Asexual Female Gametogenesis Involves Contact with a Sexually-Fated Megaspore in Apomictic Hieracium . Issue 3 (29th May 2018) - Juranić, Martina; Tucker, Matthew R.; Schultz, Carolyn J.; Shirley, Neil J.; Taylor, Jennifer M.; Spriggs, Andrew; Johnson, Susan D.; Bulone, Vincent; Koltunow, Anna M.
Abstract : Cells initiating asexual female gametogenesis in Hieracium are marked with arabinogalactan protein epitopes and must make contact with a sexually fated functional megaspore to undergo mitosis. Abstract: Apomixis results in asexual seed formation where progeny are identical to the maternal plant. In ovules of apomictic species of the Hieracium subgenus Pilosella, meiosis of the megaspore mother cell generates four megaspores. Aposporous initial (AI) cells form during meiosis in most ovules. The sexual pathway terminates during functional megaspore (FM) differentiation, when an enlarged AI undergoes mitosis to form an aposporous female gametophyte. Then, the mitotically programmed FM dies along with the three other megaspores by unknown mechanisms. Transcriptomes of laser-dissected AIs, ovule cells, and ovaries from apomicts and AI-deficient mutants were analyzed to understand the pathways involved. The steps leading to AI mitosis and sexual pathway termination were determined using antibodies against arabinogalactan protein epitopes found to mark both sexual and aposporous female gametophyte lineages at inception. At most, four AIs differentiated near developing megaspores. The first expanding AI cell to contact the FM formed a functional AI that underwent mitosis soon after megaspore degeneration. Transcriptome analyses indicated that the enlarged, laser-captured AIs were arrested in the S/G2 phase of the cell cycle and were metabolically active. Further comparisons with AI-deficient mutants showed that AIs were enriched in transcripts encoding homologs of genes involved in, and potentially antagonistic to, known FM specification pathways. We propose that AI and FM cell contact provides cues required for AI mitosis and megaspore degeneration. Specific candidates to further interrogate AI-FM interactions were identified here and include Hieracium arabinogalactan protein family genes.